Peran Komunitas Seni Budaya dalam Pembentukan City Branding - Pupung Zulyan; Sri Dewi Setiawati (EDUTOURISM Journal Of Tourism Research, 2020)
This research aims to find out what efforts are made by the Kitchen community of art and culture of Bandung to help form City Branding. Community. Bandung's art and cultural kitchen is a community that does traditional Sundanese art and culture through tourism. The activities carried out by the community Kitchen arts and culture are expected to not only preserve traditional arts and culture but also preserve nature and improve the economy of the surrounding community. The role of The Kitchen Arts and Culture Community in the establishment of city branding Bandung city by becoming one icon of Bandung City. Starting from the preservation of traditional arts and culture that they do as a characteristic formation for the deference of marketing of traditional arts and cultures that originate from their area through tourism activities and become ambassadors representing the city of Bandung to several cities in Indonesia. For the role of the government in the establishment of city branding, it is necessary to align the objectives between the previous officials and the new officials, so that the goals made can be realized to the maximum, because often occurs when the shift in the position of existing programs needs to be re-socialized from the beginning.